Are physical effective theories the reliable strategy for achieving certain knowledge? - Szydłowski, Marek; Tambor, Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2020)
The paper presents the methodology of effective theories as a strategy used in the process of development of modern physics to reach a final theory. We present the definition and characteristic features of an effective theory, as well as the answer to the question of whether and what kind of scenario of reaching a final theory is realized by contemporary physics. We argue that the process of development of physics in the direction of a final theory is potentially final, i.e. expressible in the conceptual schema of effective theories and as such it is convergent to a final theory. In each effective theory there are physical constants, however, whose status differs from logical constants. They have a dimension (length, energy, etc.) and are used to compare physical quantities. The structure of relevant effective theory can be interpreted in the epistemological framework of approximated truth theory. In the case study of cosmological models, the sequence of models is convergent to potentially true model. The Standard Cosmological Model is the theory of the structure and dynamics of the Universe.